Analysis Of Flood Vulnerability Level Based On Geographic Information System In Tebing Siring Sub Watershed, Tabunio Watershed, Tanah Laut Regency - Hafida Dwi Rushady; Syarifuddin Kadir; Eko Rini Indrayatie (Jurnal Sylva Scienteae, 2025)
Analysis of the level of watershed damage in 2009 in watersheds in the BPDAS Barito working area stated that the Tabunio watershed is included in the second priority handling watershed in South Kalimantan Province because it is considered one of the critical watersheds.  Flooding is an event that occurs due to poor water and critical land management conditions and due to high rainfall in the upstream and middle watersheds or abnormal catchment areas. This study aims to determine the potential level of flood vulnerability in the Tebing Siring Sub-Watershed of Tabunio Watershed. The method used is purposive sampling, scoring with overlay union. Purposive is performed for infiltration sampling. Scoring in GIS applications is the provision of weights or values to the map polygons of each parameter in a series of spatial analysis. An overlay process is carried out on all parameters with the "union" tool in Arcgis. The results showed that the distribution of flood vulnerability levels in the Tebing Siring Sub-watershed at the highest level was 7,414,115 with the category less prone to spreading evenly at the locations of tebing siring 1, tebing siring 2, and tebing siring 3. The level of flood vulnerability is prone to be the second widest at 817.7462 ha, and the category is somewhat vulnerable to an area of 740.361 ha. The level of flood vulnerability with the smallest area with the category of not vulnerable, which is 470.0998 ha.